PENGARUH SOLVABILITAS, KEPEMILIKAN PUBLIK, AUDITOR SWITCHING DAN PERUSAHAAN HOLDING TERHADAP AUDIT DELAY - Syah, Encik Sonya Maretha; Wiguna, Meilda; ', Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyze the factors that affect audit delay. The examined factors of this research are solvability, public ownership, auditor switching and holding company as the independent variables while the audit delay as the dependent variables. The sample consists of 28 mining companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports consistently in the period 2011-2014. The data that was used in this research was secondary data and selected by using purposive sampling method. The analysis tool used multiple regression analysis. The test results show that solvability have significant effect on audit delay, while public ownership, auditor switching and holding company had no effect on the provision of the audit delay.Keyword : audit delay, solvability, public ownership, auditor switching and holding company.